Predicting the impact of increasing carbon dioxide concentration and temperature on seed germination and seedling establishment of African grasses in Brazilian Cerrado. (14th July 2015) - de Faria, Ana Paula; Fernandes, Geraldo Wilson; França, Marcel Giovanni Costa
Abstract: Global climate changes and biological invasions are environmental disturbances that may interact synergistically, causing loss of biodiversity. As the early stages of development are the most sensitive and easily affected by these constraints, this study investigated the effects of increased carbon dioxide (CO2 ) and temperature, as forecasted for 2100, on seed germination and early development of three species of invasive African grasses that have gradually replaced landscapes of the Brazilian Cerrado biome. It was observed that these parameters affected percentage and rate of germination in U rochloa brizantha, rate of germination and mean germination time in U rochloa decumbens and accelerated autotrophy acquisition in U. brizantha, U. decumbens and Megathyrsus maximus . Regarding root elongation, all species showed changes in total length, absolute and relative growth rate, but at different stages of development or time intervals, with increased temperature being more significant than increased CO2, probably due to seed reserves still being the main carbon sources at this stage. Taken together, the results indicate that the effects of CO2 and increased temperature are species specific and highlight the greatest potential of U . brizantha to germinate, and of U . decumbens for seedling establishment under these environmental changes.